2019
DOI: 10.1038/s41598-019-39427-4
|View full text |Cite
|
Sign up to set email alerts
|

Ibudilast sensitizes glioblastoma to temozolomide by targeting Macrophage Migration Inhibitory Factor (MIF)

Abstract: Recurrence in patients with glioblastoma (GBM) is inevitable resulting in short survival times, even in patients with O-6-Methylguanine-DNA Methyltransferase ( MGMT ) methylation. Other pathways must be activated to escape from temozolomide (TMZ) treatment, however acquired resistance mechanisms to TMZ are not well understood. Herein, frozen tumors from 36 MGMT methylated patients grouped according to overall survival were extracted and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
(49 reference statements)
0
31
0
Order By: Relevance
“…Ibudilast is an agent that is able to diffuse the blood-brain barrier (BBB), developing antitumor activity by inhibiting MIF and phosphodiesterase-4 (PDE-4), also reducing TLR-4 downsignaling with pro-oncogenic properties. Action leads to excessive apoptosis and the limitation of cell proliferation in GBM [196][197][198]. Ibudilast was also observed in trials, including neuroinflammation, amyotrophic lateral sclerosis (ALS), dysphoria, treatment of alcohol-use disorders, and methamphetamine dependence (https://clinicaltrials.gov/ct2/results?cond=ibudilast&term=&cntry=&state=&city=&dist=).…”
Section: Tlr-4 In Glioblastoma Multiforme-clinical Applicationmentioning
confidence: 99%
“…Ibudilast is an agent that is able to diffuse the blood-brain barrier (BBB), developing antitumor activity by inhibiting MIF and phosphodiesterase-4 (PDE-4), also reducing TLR-4 downsignaling with pro-oncogenic properties. Action leads to excessive apoptosis and the limitation of cell proliferation in GBM [196][197][198]. Ibudilast was also observed in trials, including neuroinflammation, amyotrophic lateral sclerosis (ALS), dysphoria, treatment of alcohol-use disorders, and methamphetamine dependence (https://clinicaltrials.gov/ct2/results?cond=ibudilast&term=&cntry=&state=&city=&dist=).…”
Section: Tlr-4 In Glioblastoma Multiforme-clinical Applicationmentioning
confidence: 99%
“…By contrast, MIF signaling through CXCR2 primarily through PI3K/Akt-dependent signaling with Ca transients (41). The pharmacologic targeting of MIF has also been of great interest in a variety of inflammatory conditions including multiple sclerosis, systemic lupus erythrematosus, rheumatoid arthritis, inflammatory bowel disease, and other inflammatory disorders (32,(42)(43)(44)(45)(46)(47)(48)(49). Additionally, clinically approved MIF inhibitors have been developed that could potentially be repurposed for GBM (42).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the anti-MIF monoclonal antibodies were effective in vitro and in vivo in prostate cancer and colon cancer models [15,78]. In addition, add on treatment to temozolomide with the MIF inhibitor ibudilast significantly increased the survival in vivo, in a patient-derived xenograft model of glioblastoma [56].…”
Section: Chemotherapeutic Action Of Mif And/or Ddt Inhibitors In Precmentioning
confidence: 98%
“…Numerous preclinical and clinical studies have demonstrated that MIF is overexpressed and may correlate with tumor aggressiveness in many different types of human cancers such as prostate , bladder, and kidney cancer [30], cervical cancer [20], ovarian cancer [44,45], breast cancer [29], gastric cancer [29], hepatocellular carcinoma [46], colon cancer [47,48], pancreatic cancer [49,50], gallbladder cancer [51], lung cancer [29,52], melanoma [31], head and neck cancer [29], acute myeloid leukemia [53,54], glioblastoma [15,55,56], and NB [57][58][59][60]. Moreover, elevated MIF expression is correlated with a worse patient overall survival in a large variety of cancers such as breast cancer [29], gastric cancer [29], hepatocellular carcinoma [61], pancreatic cancer [49,50], metastatic melanoma [31], head and neck cancer [29], esophageal squamous cell carcinoma [62], acute myeloid leukemia [53], glioblastoma [29,56], and NB [57]. However, conflicting results have also been reported and other studies have shown that, in other types of tumors, endogenous MIF may possess a beneficial anticancer activity.…”
Section: Mif and Cancermentioning
confidence: 99%